Importance of the application of the new budget classification catalog, in the mayoralty of the municipality of La Calera, in 2020 (2020)
The implementation of the new budget classifier is a step forward to the Public Finances and the state modernization, the finance ministry and the public credit as the pioneer of the budget in Colombia has been making great contributions in order to allow to the Colombian state the integration and/or consolidation of the achievement and execution of public resources. Consolidate the efficient management of an entire country in order to improve the wellbeing of citizens, the globalization of information and the reporting of clear, timely and efficient information, facilitating the understanding and analysis of the country's finances and efficient fiscal policy evaluation; this at the Nation level; At the territorial level, it is a challenge that the Legal Representatives have to face and fulfill, together with their advisers and officials, since from their Development Plan proposed in the campaign and with which they obtained the votes to come to govern the entities, it is closely linked to the budget. Now, the execution of the resources for the four-year term of his administration takes the guideline of this development plan, which must be incorporated into the medium-term Fiscal Framework and the Multi-Annual Investment Plan, then to each of the budget items, taking into account the resources, be they their own, transfers, or agreements; likewise, the priority lines in each sector, and in this way, the necessary adjustments must be made in order to comply with this development plan, which in the end and Cape is the baseline taken for resource execution. On the other hand, there is the level of compliance, execution and own effort made by the entities, since this is also a standard that will allow them to demonstrate what their level of management was, allowing the entity to comply with the provisions of Law 617 of 2000 regarding the categorization and execution of resources.